Trend Analysis of Domestic Tourist Visits to Bali Post-Covid-19 Pandemic - I Gusti Made Riko Hendrajana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Bali is one of the most popular tourist destinations by tourists, because its natural and cultural charms make this tourist destination increasingly popular. Therefore, most of the income of the Province of Bali relies on the tourism sector. However, the onslaught of the COVID-19 pandemic has had an impact on decreasing tourist visits, including domestic tourists. Even though in this pandemic situation, income from domestic tourists is very reliable. Based on these reviews, thenThe purpose of this study is to analyze the trend of domestic tourists visiting Bali after the COVID-19 pandemic. The results of the study concluded thatThe comparison of the number of tourist visits during the COVID-19 and post-covid-19 pandemics is quite significant, especially in April to June. In April - June 2020 the number of tourist visits tends to be lower when compared to April - June 2021. Meanwhile, after the pandemic in April - June 2022, the number of visits is much higher when compared to the previous 2 years. This research is expected to be a contribution in determining policies for the Bali provincial government in restoring Bali tourism.